Discovery of a Selective 6-Hydroxy-1, 4-Diazepan-2-one Containing Butyrylcholinesterase Inhibitor by Virtual Screening and MM-GBSA Rescoring - You Zhou; Yanyu Hu; Xin Lu; Hongyu Yang; Qihang Li; Chenxi Du; Yao Chen; Kwon Ho Hong; Haopeng Sun (SAGE Publishing, 2020)
Alzheimer disease (AD) is the most common form of dementia characterized by the loss of cognitive abilities through the death of central neuronal cells. In this study, structure-based virtual screens of 2 central nervous system-targeted libraries followed by molecular mechanics/generalized born surface area rescoring were performed to discover novel, selective butyrylcholinesterase (BChE) inhibitors, which are one of the most effective therapeutic strategies for the treatments in late-stage AD. Satisfyingly, compound 5 was identified as a highly selective low micromolar inhibitor of BChE (BChE IC 50 = 1.4 μM). The binding mode prediction and kinetic analysis were performed to obtain detailed information about compound 5. Besides, a preliminary structure-activity relationship investigation of compound 5 was carried out for further development of the series. The present results provided a valuable chemical template with a novel scaffold for the development of selective BChE inhibitors.